Perbedaan Contract Relax Streching Dan Myofacial Release Technique Pada Nyeri Trigger Point Syndrome Otot Upper Trapezius - Tryani, Rina; , Agus Widodo, S.Fis., M.Fis; , Totok Budi Santoso, SST.FT, MPH (2015)
Introduction: Myofascial Trigger Point Syndrome (MTPS) is one of the conditions that can bring in addition to causing pain originating from nerves, bones and joints. MTPS itself is a syndrome that arise due to teraktifasinya one or more trigger points in the muscle fibers. Provision of therapeutic modalities for myofacial upper trapezius trigger point in select that contract relax stretching and myofascial release technique. Purposes: This study aimed to determine differences in contract relax stretching and myofascial release technique, trigger point pain syndrome in the upper trapezius muscle. Methods: This study used a quasi exsperimental design, with the approach of pre-test and post-test two design groups. The population in this study are employees of sub-district Puskesmas Panjalu Ciamis who have diagnosed with myofacial upper trapezius trigger point, the total respondents as many as 10 people, with as many details of group I and group II 5 by 5 people. Testing is done by using the value of the pain VAS. Results were analyzed using the Wilcoxon test and Mann Whitney test. Results: Statistical test using the Wilcoxon test for hypothesis 1 and 2. The Mann Whitney test for hypothesis 3. On the hypothesis 1 and 2 obtained p value: 0.043 or p <0.05 so there is the effect of Contract Relax Stretching and Myofascial Release Technique on reducing myofascial trigger point pain upper trapezius muscle. In the third hypothesis, the value of p: 0.000 or p <0.05 which means there is a significant difference Contract Award Relax Stretching and Myofascial Release Technique to myofascial trigger point pain reduction upper trapezius muscle.Conclusion: The use of Myofascial Release Technique is better than using the Contract Relax Stretching in reducing pain myiofacial upper trapezius muscle trigger points. Keywords: Contract Relax Stretching, Myofascial Release Technique, myofacial upper trapezius muscle trigger point.